2016
DOI: 10.1021/acs.chemrev.6b00057
|View full text |Cite
|
Sign up to set email alerts
|

Organic Photoredox Catalysis

Abstract: In this review, we highlight the use of organic photoredox catalysts in a myriad of synthetic transformations with a range of applications. This overview is arranged by catalyst class where the photophysics and electrochemical characteristics of each is discussed to underscore the differences and advantages to each type of single electron redox agent. We highlight both net reductive and oxidative as well as redox neutral transformations that can be accomplished using purely organic photoredox-active catalysts.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

23
2,888
3
49

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 4,772 publications
(3,097 citation statements)
references
References 599 publications
(1,014 reference statements)
23
2,888
3
49
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9] Ru-and Ir-based coordination complexes have received enormous attention because of their excellent visible-light-harvesting properties, modest to extremely high oxidation and reduction potentials, relatively long excited-state lifetimes, and reasonably good chemical and photostabilities under synthetic oxidative and reductive conditions. [2] In addition, considerable efforts have been made to develop metal-free photoredox catalytic methods with organic dyes [8,[10][11][12][13][14] such as eosin Y [10,11] or rhodamine derivatives [13,14] and organic heterogeneous photocatalysts [15] for synthetic transformations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7][8][9] Ru-and Ir-based coordination complexes have received enormous attention because of their excellent visible-light-harvesting properties, modest to extremely high oxidation and reduction potentials, relatively long excited-state lifetimes, and reasonably good chemical and photostabilities under synthetic oxidative and reductive conditions. [2] In addition, considerable efforts have been made to develop metal-free photoredox catalytic methods with organic dyes [8,[10][11][12][13][14] such as eosin Y [10,11] or rhodamine derivatives [13,14] and organic heterogeneous photocatalysts [15] for synthetic transformations.…”
Section: Introductionmentioning
confidence: 99%
“…Quinones [8,16,17] occur in nature and are known for their excellent electron-accepting and hydrogen-abstracting abilities. [16,18] Not surprisingly, different quinone derivatives have been used for photo-oxidative transformations under visible light.…”
Section: Introductionmentioning
confidence: 99%
“…To accomplish this goal, we selected the methyl acridinium perchlorate 4 ( E* 1/2 =+2.06 V vs. SCE)3c, 17 as the photoredox catalyst and evaluated a range of solvents and bases under blue LED irradiation. Pleasingly, in the presence of an aryl‐disulfide as H‐atom relay catalyst,18 and 2,6‐lutidine as the base, 5 a was obtained in 81 % yield, which, to the best of our knowledge, represents the first fully catalytic radical hydroimination of olefins.…”
mentioning
confidence: 99%
“…14,15 Recently, however, it was shown that in certain cases, simple and inexpensive organic dyes could be used as photoredox catalysts, thus making the processes greener and more suitable for large scale pharmaceutical production. 16 For example, Zeitler et al performed organocatalytic α-alkylation of aldehydes in the presence of eosin Y, which originally exploited Ru(bpy) 3 Cl 2, 17 giving the desired products with similar yields and enantiomeric excesses. 18 Hence, we envisaged that the visible-light driven oxyamination reaction described could be realized with organic dyes eliminating the need for the use of precious metal complexes.…”
Section: -68%mentioning
confidence: 99%